The Influence of Facilities on Visitors' Emotional Value at Mifan Water Park Tourist Attraction in Padang Panjang City - Zendlyve Furqon; Dwi Pratiwi Wulandari (Pt. Threeple Herphi Educate, 2025)
This study investigates the effect of tourist facilities on visitors’ emotional value at Mifan Water Park, Padang Panjang, Indonesia. Using a quantitative, causal-associative design, data were gathered from 379 respondents via structured questionnaires. Tourist facilities were measured by indicators such as cleanliness, functionality, and availability, while emotional value encompassed comfort, enjoyment, and satisfaction. The regression analysis revealed a strong and statistically significant relationship (β = 1.856, p < 0.001), with an adjusted R² of 0.808, indicating that approximately 80.8% of the variation in emotional value can be explained by the perceived quality of facilities. Despite slight heteroscedasticity and non-normal residuals, classical assumption tests confirmed the model’s reliability. The findings emphasize that facility improvements are critical for enhancing emotional experiences and competitive positioning in regional tourism markets. This study contributes to the literature by contextualizing the role of physical environment in emotional value creation at localized water-based attractions in Southeast Asia.